2016
DOI: 10.1017/jfm.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

Critical torsional modes of convection in rotating fluid spheres at high Taylor numbers

Abstract: A numerical study of the onset of convection in rotating, internally heated, selfgravitating fluid spheres is presented. The exploration of the stability of the conduction state versus the Taylor and the Prandtl numbers supplies a detailed idea of the laws that fulfil the four types of solutions obtained at low Prandtl numbers. The main result found is that axisymmetric (torsional) modes of convection are preferred at high Taylor numbers in the zero-Prandtl-number limit. This instability appears at low Rayleig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 24 publications
5
27
0
Order By: Relevance
“…Then the behavior is very close to that of the eigenfunction at the onset of convection (see Ref. [17]), with an almost complete exchange of kinetic energy between the toroidal and poloidal components because they are a quarter period out of phase, their mean value and amplitude are the same, and the minimum is almost zero. This is why the two curves represented in each plot of Fig.…”
Section: Results: Periodic Solutionssupporting
confidence: 62%
See 2 more Smart Citations
“…Then the behavior is very close to that of the eigenfunction at the onset of convection (see Ref. [17]), with an almost complete exchange of kinetic energy between the toroidal and poloidal components because they are a quarter period out of phase, their mean value and amplitude are the same, and the minimum is almost zero. This is why the two curves represented in each plot of Fig.…”
Section: Results: Periodic Solutionssupporting
confidence: 62%
“…In the case of shells, it was found that at low Ekman numbers (E) it is possible to find nonaxisymmetric and equatorially antisymmetric modes at the beginning of convection for the very small Prandtl numbers (Pr < 0.01) of the liquid metals [16]. Moreover, preferred torsional modes, i.e., axisymmetric and equatorially antisymmetric modes, were found numerically in rotating fluid spheres for Pr 0.01 at low E [17]. This latter result was confirmed analytically by using asymptotic methods in Ref.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The main characteristic is that the patterns of convection depend on the value of σ , and the preferred eigenfunctions are even axisymmetric in the σ → 0 limit [60].…”
Section: Results On the Stability Analysismentioning
confidence: 99%
“…In this paper, we vary Pr between [10 −2 , 10 −1 ]. Note that for small Prandtl numbers, convection cells attached to the equator of the outer sphere are preferred to thermal Rossby waves at the linear onset of convection when the Ekman number is moderately small (Zhang & Busse, 1987;Busse & Simitev, 2004;Plaut & Busse, 2005;Sánchez et al, 2016). In the limit Ek 1 and Ek /Pr 1, the critical Rayleigh number at the onset of these equatorially-attached modes scales as Ek −2 , while the critical Rayleigh number at the onset of the thermal Rossby waves scales as Ek −4/3 (Busse & Simitev, 2004).…”
Section: Introductionmentioning
confidence: 99%